Cross-platform desktop applications : using Node, Electron, and NW.js - Jensen, Paul B. (Manning Publications, 2017)
Cross-Platform Desktop Applications guides you step-by-step through creating Node.js desktop applications with NW.js and Electron from GitHub. About the Technology Desktop application development has traditionally required high-level programming languages and specialized frameworks. With Electron and NW.js, you can apply your existing web dev skills to create desktop applications using only HTML, CSS, and JavaScript. And those applications will work across Windows, Mac, and Linux, radically reducing development and training time. About the Book Cross-Platform Desktop Applications guides you step by step through the development of desktop applications using Electron and NW.js. This example-filled guide shows you how to create your own file explorer, and then steps through some of the APIs provided by the frameworks to work with the camera, access the clipboard, make a game with keyboard controls, and build a Twitter desktop notification tool. You'll then learn how to test your applications, and debug and package them as binaries for various OSs. What's Inside Create a selfie app with the desktop camera Learn how to test Electron apps with Devtron Learn how to use Node.js with your application About the Reader Written for developers familiar with HTML, CSS, and JavaScript. About the Author Paul Jensen works at Starcount and lives in London, UK.